Effects of Phytase Super Dosing on Performance, Plasma Mineral Contents and Bone Mineralization in Broiler Chicken - Hossain, S.; Hossain, M.A.; Akter, N.; Akter , M. (International Journal of Poultry Science, 2022)
Objectives: This experiment evaluated the effect of phytase super dosing on performance, tibia bone quality and serum biochemistry of broiler chicken. Materials and Methods: A total of 96 day-old chicks were distributed randomly into four treatment groups: D0, D1, D2, D3 with four replicates per treatment (6 chicks per replicate). The treatments were control diet (D0), control diet +500 FTU phytase kg–1 (D1), control diet +1500 FTU phytase kg–1 (D2) and control diet +2500 FTU phytase kg–1 (D3), that were fed to the birds from day 13-28. Birds were offered a commercial starter diet from day 0-12. Results: The different levels of phytase had no significant effect on body weight gain (BWG) and feed intake (FI). Supplementation of 1500 FTU phytase kg–1 of diet showed better (p<0.05) FCR than those received 2500 FTU phytase kg–1 of diet. Diet with 1500 FTU phytase kg–1 increased (p<0.05) the serum concentration of phosphorus (P) and total protein (TP). Inclusion of 1500 FTU phytase kg–1 of diet increased (p<0.05) the calcium (Ca) content of tibia. Diets supplemented with 500 and 1500 FTU phytase kg–1 reduced (p<0.05) the heart weight but increased (p<0.05) the drumstick weight of birds. Supplementation of 500 and 1500 FTU phytase kg–1 diet significantly reduced the total feed cost, production cost and increased the total profit kg–1 live bird. Conclusion: Supplementing diets with 500 and 1500 FTU phytase kg–1 improved the overall production performance of broiler chickens and consequently enhanced economic profitability.